Comment to Lehrmann et al. New sections and observations from the Nanpanjiang Basin, South China - Kershaw, S; Collin, PY; Crasquin, S (PALAIOS, 2016)
In the study of Earth-surface environmental processes during the events associated with the Permian–Triassic boundary, a key issue is the nature of the latest Permian pre-extinction surface in shallow marine limestones in numerous sites, principally within the Tethyan realm. Sediments below this surface pre-date the extinction event, so that the limestones comprising these latest Permian facies contain diverse fossil remains of organisms that lived just before the extinction. At all reported sites, this surface is disconformably overlain by post-extinction sediments, which contain microbialites in many places, particularly in Tethys. The nature of the youngest pre-extinction surface remains controversial, originating by either physical erosion or dissolution. Furthermore, if the surface was created by dissolution, this could reflect ocean acidification or, alternatively, subaerial dissolution. These arguments were discussed by Collin et al. (2009) and Kershaw et al. (2012a).